EXPRESSION OF THE MORPHOLOGICAL GENDER IN A FOREIGN LANGUAGE IN MODERN TIMES - Shakirova, Saida (Журнал иностранных языков и лингвистики, 2023)
Our article analyzes and examines scientific works, on the expression of morphological sex in a foreign language in modern times, which is edited by scientists.